Beads for sustained-release active composition and preparation method and application thereof

By using organic gel beads of sustained release active composition in toothpaste, the damage to dentin by the friction agent and the stability of the active substance is solved, and the toothpaste with low copper consumption and high cleaning power is achieved to ensure the stability and long-lasting effect of the active substance.

CN119033657BActive Publication Date: 2025-04-04SAVITA (GUANGZHOU) HEALTH PHARM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411153475.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-04-04
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The friction agent in existing toothpastes has a great damage to dentin and enamel, and the active substances are prone to degradation when environmental changes and react with other components, resulting in a decrease in stability and effect.

Method used

Organic gel beads of a sustained-release active composition are used to reduce the amount of inorganic friction agent added by compounding in toothpaste, and a stable polysaccharide carrier is formed using ingredients such as edible gel and sodium alginate, and the filling components such as mica is used for buffering, ensuring stable coating and sustained release of the active ingredients.

Benefits of technology

Toothpaste with low copper consumption and high cleaning power is achieved, reducing the damage to dentin by inorganic friction agents, ensuring the stability and long-lasting effect of active substances, and improving the cleaning power and antibacterial and anti-inflammatory capabilities of toothpaste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005004246630000051
    Figure BDA0005004246630000051
  • Figure BDA0005004246630000052
    Figure BDA0005004246630000052
  • Figure BDA0005004246630000061
    Figure BDA0005004246630000061
Patent Text Reader

Abstract

The present invention discloses beads of a sustained-release active composition and a preparation method and application thereof, which specifically belong to the technical field of abrasives for toothpaste; the beads include components: an active composition, a colloid component, a filling component, a moisturizer, a preservative and a solvent; the active composition is a root extract of Bletilla striata, amelogenin and an extract of Alpinia oxyphylla; the colloid component is composed of sodium alginate and edible gum; the filling component is composed of mica, titanium dioxide and iron oxide; the moisturizer is glycerol, propylene glycol, sodium hyaluronate and Tremella fuciformis polysaccharide. The beads of the sustained-release active composition provided by the present invention have mild friction without irritation, little damage to tooth enamel, and at the same time have the efficacy of the sustained-release active composition, achieving the effects of good cleaning power, anti-inflammatory and antibacterial, and repairing tooth enamel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of abrasives for toothpaste, and in particular relates to beads of a sustained-release active composition and a preparation method and application thereof. Background Art

[0002] Toothpaste is a mixture with complex ingredients and uniform distribution. One of its main ingredients is abrasives. Abrasives are solid raw material ingredients in toothpaste that can work with toothbrushes to wipe off soft deposits on the surface of teeth and reduce foreign substances such as tooth stains, dental plaque, and tartar. It is generally a powdered solid that is insoluble in water, with moderate particles and texture, and does not damage tooth enamel and dentin. Commonly used abrasives are mainly calcium carbonate, calcium hydrogen phosphate, and hydrated silica. The particles of calcium carbonate in these abrasives are mostly square rhombuses, and the particles of calcium hydrogen phosphate and hydrated silica are mostly spherical. They all have a certain hardness, and are less deformed during friction, and cannot penetrate into the gaps between teeth and the pits and grooves of teeth for cleaning.

[0003] Ordinary toothpaste faces many challenges in maintaining the stability of active ingredients during the shelf life. The active substances themselves may be sensitive to environmental conditions and easily degraded due to changes in light, temperature, humidity or reactions with other ingredients in the toothpaste, resulting in reduced effectiveness. Chemical instability may cause the structure of the active substances to change and lose their original efficacy. At the same time, the risk of microbial contamination increases, which may cause toothpaste corruption and reduce the effectiveness of active substances. Physical stability issues, such as uneven dispersion or aggregation, can also affect the release of active substances and the overall performance of toothpaste. In addition, factors such as pH value, salt concentration, packaging and storage conditions will affect the stability of active substances. Consumer usage habits, such as frequent opening of the lid, may also pose a threat to stability.

[0004] Therefore, the present invention mainly studies an organic gel bead with low copper consumption value, high cleaning power and the ability to slowly release active composition, which can be compounded with existing abrasives to reduce the amount of inorganic abrasives added and reduce the damage of inorganic abrasives to dentin and enamel. At the same time, it can effectively and stably encapsulate the active substance so that the active substance can be stably preserved in the toothpaste. During the toothpaste cleaning process, the active substance can also accurately act on the tooth body and gums as the beads rub against the teeth. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide an organogel bead with low copper loss value, high cleaning power and the ability to slowly release an active composition.

[0006] To achieve the above object, the present invention discloses the following technical solutions:

[0007] In a first aspect, the present invention provides a bead for sustained release of an active composition, comprising components: an active composition, a colloid component, a filling component, a moisturizer, a preservative, a chelating agent, and a solvent;

[0008] The active composition is at least one of a Bletilla striata root extract, amelogenin and an Alpinia oxyphylla seed extract;

[0009] The colloid component is composed of sodium alginate and edible glue;

[0010] The edible gum includes at least one of carrageenan, xanthan gum, guar gum, agar, gelatin, locust bean gum or gellan gum;

[0011] The filling components are composed of mica, titanium dioxide and iron oxide;

[0012] The moisturizing agent is at least one of glycerin, propylene glycol, sodium hyaluronate, and Tremella polysaccharide;

[0013] The preservative is at least one of phenoxyethanol, methylparaben, p-hydroxyacetophenone, and caprylhydroxamic acid;

[0014] The solvent is water.

[0015] Preferably, the sodium alginate is added to the beads in an amount of 0.25-2.0 wt %;

[0016] The amount of edible glue added to the beads is 0.5-2.0wt%,

[0017] Preferably, the filling component is added to the beads in an amount of 0.1-2.0 wt%.

[0018] Further preferably, the combination of edible gums in the colloid component is a combination of xanthan gum, gellan gum and agar;

[0019] The mass ratio of xanthan gum, gellan gum and agar is (0.1-1):(1-2):(1-2)

[0020] Further preferably, the mass ratio of mica, titanium dioxide and iron oxide in the filling component is (65-87):(5-16):(8-19).

[0021] Preferably, the particle size of the beads is 1000-4000 μm.

[0022] In a second aspect, the present invention provides a method for preparing beads of the sustained-release active composition according to the first aspect, comprising the following steps:

[0023] S1. Mix deionized water, sodium alginate and edible gum and heat to 80-100°C to dissolve to obtain a mixed solution A;

[0024] S2. The active composition was uniformly dissolved in deionized water to obtain a mixed solution B;

[0025] S3. The filling component, preservative, and moisturizer are added to the mixed solution A and mixed evenly to obtain a mixture C;

[0026] S4. The mixed solution B obtained in step S2 is added to the mixed solution C, and the mixture is stirred and dispersed uniformly to obtain a mixed solution D;

[0027] S5. The mixed solution D is dripped into the incompatible condensation reaction solution through a dripping device to quickly form gel beads. The formed beads are washed with water and then sealed and immersed in a preservative solution to obtain the beads of the sustained-release active composition.

[0028] In a third aspect, the present invention provides a toothpaste comprising beads of the sustained-release active composition of the first aspect;

[0029] The beads are added in an amount of ≤50 wt % in the toothpaste.

[0030] Furthermore, it also contains abrasives, moisturizers, foaming agents, thickeners, aromatics, preservatives, anti-tartar agents, pH regulators, sweeteners, anti-caries agents, and solvents.

[0031] In a fourth aspect, the present invention provides the use of the beads of the sustained-release active composition described in the first aspect in the preparation of an oral cleaning preparation having anti-caries, anti-inflammatory and antibacterial effects.

[0032] The beads of the sustained-release active composition provided by the present invention can continuously release active ingredients: the design of the sustained-release beads enables the active ingredients (such as Bletilla striata root extract, amelogenin and Alpinia oxyphylla extract) in the sustained-release beads to be slowly and continuously released into the oral environment during the friction between the toothpaste and the teeth. This slow-release mechanism helps to improve the effect and durability of the active ingredients. Improve the physical properties of the toothpaste: the beads of the sustained-release active substance have a certain friction force and excellent cleaning power, and the reasonable combination of the edible gum components makes the entire system of the sustained-release beads have a certain coating and stability, forming a polysaccharide carrier with a coating effect and stability, and the mica in the filling component can effectively buffer the friction between titanium dioxide and the abrasive in the toothpaste itself, slowing down the wear of titanium dioxide on tooth enamel, while also playing a cleaning role.

[0033] The bletilla striata root extract in the active ingredients provided by the invention has the effects of anti-inflammatory and promoting oral tissue repair; amelogenin helps to protect tooth enamel; the Alpinia oxyphylla extract contains nutrients beneficial to oral health and has a promoting effect on the bletilla striata root extract, thereby improving the anti-inflammatory and antibacterial effects of the bletilla striata root extract.

[0034] The slow-release beads provided by the present invention improve the functionality of toothpaste: The slow-release bead technology can make toothpaste have more diverse functions, such as antibacterial, anti-inflammatory, whitening, repairing, etc., to meet the needs of different consumers. The slow-release bead technology helps to reduce the occurrence of oral problems such as gingivitis and bad breath by continuously releasing active ingredients.

[0035] Beneficial effects of the present invention:

[0036] The beads of the sustained-release active composition provided by the present invention are an organic gel mixture, which is greatly different from the inorganic abrasives of traditional toothpaste and is characterized by gentle friction without irritation and little damage to tooth enamel. At the same time, it has the efficacy of the sustained-release active composition, achieving the effects of good cleaning power, anti-inflammatory and antibacterial properties, and repairing tooth enamel. DETAILED DESCRIPTION

[0037] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0038] The experimental methods used in the embodiments and comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used are all commercially available unless otherwise specified; the percentages mentioned in the embodiments and comparative examples are all mass percentages unless otherwise specified.

[0039] In the present invention:

[0040] Bletilla striata root extract: Bletilla striata root extract, INCI name is Bletilla striata ROOT EXTRACT, purchased from Ningxia Vanilla Biotechnology Co., Ltd.;

[0041] Amelogenin: purchased from Guangzhou Dongfang Biotechnology Co., Ltd.

[0042] Alpinia oxyphylla extract: Alpinia oxyphylla extract, INCI name ALPINIAOXYPHYLLA EXTRACT, purchased from Zhengzhou Sumu Yunling Biotechnology Co., Ltd.

[0043] Mica: purchased from Sanbao New Materials Technology Co., Ltd.;

[0044] Titanium dioxide: purchased from Henan Longxing Titanium Technology Co., Ltd.;

[0045] The remaining raw materials are commercially available.

[0046] Preparation of sustained release active composition beads:

[0047] Accurately weigh the raw materials according to the mass percentage or mass fraction in Table 1;

[0048] Step S1, mixing deionized water, sodium alginate and edible gum and heating to 80-100° C. to dissolve to obtain a mixed solution A;

[0049] Step S2, dissolving the active composition uniformly with deionized water to obtain a mixed solution B;

[0050] Step S3, adding the filling component, preservative, and moisturizer into the mixed solution A and mixing them evenly to obtain a mixture C;

[0051] Step S4. Add the mixed solution B obtained in step S2 to the mixed solution C, and stir and disperse them uniformly at 5000-10000 r / min and 80-100° C. to obtain a mixed solution D;

[0052] S5. The mixed liquid D is dripped into the incompatible condensation reaction liquid through a dripping device to quickly form gel beads. The formed beads are washed with deionized water and then sealed and immersed in a preservative solution to obtain beads 1-14 of the sustained-release active composition; wherein the incompatible condensation reaction liquid is silicone oil, the condensation temperature is -60°C, the particle size of the sustained-release beads is controlled to be 1000-4000μm, and the preservative solution is prepared from phenoxyethanol, methylparaben and 95v / v% ethanol aqueous solution.

[0053] The specific bead numbers of the sustained-release active composition in Table 1 correspond to the addition amounts of specific raw materials.

[0054] Table 1. Mass percentage of raw materials for the preparation of sustained-release beads

[0055]

[0056] Table 1. Mass percentage of raw materials for the preparation of sustained-release beads (continued)

[0057]

[0058]

[0059] Note: “-” in the table means not added.

[0060] Slow-release beads 5:

[0061] The edible gum component lacks xanthan gum, and the rest is consistent with the slow-release beads 4;

[0062] Slow-release beads 6:

[0063] The edible gum component lacks gellan gum, and the rest is consistent with the sustained-release beads 4;

[0064] Slow-release beads 7:

[0065] The edible gum component lacks agar, and the rest is consistent with slow-release beads 4;

[0066] Slow-release beads 8:

[0067] The edible gum components lack gellan gum and agar, and the rest are consistent with slow-release beads 4;

[0068] Slow-release beads 9:

[0069] The edible gum component lacks xanthan gum and agar, and the rest is consistent with slow-release beads 4;

[0070] Slow-release beads 10:

[0071] The edible gum component lacks xanthan gum and gellan gum, and the rest is consistent with the slow-release beads 4; slow-release beads 11:

[0072] The filling components lack titanium dioxide and iron oxide, and the rest are consistent with sustained-release beads 4; sustained-release beads 12:

[0073] The filling component lacks mica, and the rest is consistent with the sustained-release beads 4;

[0074] Slow-release beads 13:

[0075] The mica was replaced by silica in the filling component, and the rest was the same as that of the sustained-release beads 4;

[0076] Slow-release beads 14:

[0077] In the filling component, titanium dioxide is replaced by silicon dioxide, and the rest is the same as that of sustained-release beads 4.

[0078] Performance Testing

[0079] Prepare the control group toothpaste and the experimental group toothpaste according to the raw materials in Table 2;

[0080] Table 2 Raw materials for the preparation of toothpaste in the control group and experimental group

[0081]

[0082]

[0083] Note: “-” in the table means not added.

[0084] Toothpaste copper loss value test

[0085] Experimental principle: The greater the copper consumption value of toothpaste, the greater the loss of tooth enamel by the abrasive in the toothpaste. However, the lower the copper consumption value, the worse the abrasive performance on teeth and the worse the cleaning power on tooth surface plaque. Therefore, the copper consumption value should be within an appropriate range (2.0-3.0 mg) to ensure the cleaning power while minimizing the loss of tooth enamel.

[0086] Experimental plan: Dilute the toothpaste of the control group and the experimental group with deionized water in a ratio of 1:1, and pour into the material pool in the copper loss tester to immerse the copper sheet. Perform 10,000 friction tests on the copper sheet. Weigh the difference before and after the friction of the copper sheet, which is the copper loss value. Repeat 5 times for each group and take the average value. The results are shown in Table 3.

[0087] Evaluation of the efficacy of toothpaste in removing exogenous stains

[0088] The experiment referred to the test method of "T / COCIA 7-2020 Laboratory Evaluation Method for the Effectiveness Evaluation of Toothpaste for Oral Cleaning and Care Products for Removing Exogenous Stains". After the toothpastes of the experimental and control groups were prepared into toothpaste slurries, the enamel module was brushed 800 times on the L8-Ⅱ type brush grinder. The spectrophotometer was used to measure the change in the whiteness value of the enamel area before and after the brushing test. The color index of the enamel is expressed by the L* value of the CIE L*a*b* color space. The larger the L* value, the lighter the color and the higher the whiteness value. The toothpaste slurry was prepared at a mass ratio of toothpaste to water of 1:1.6. The difference ΔL between the enamel of the experimental and control groups before and after brushing was * (ΔL*=L* 后 -L* 前 ), the larger the difference is, the better the effect of removing exogenous spots is. The results are shown in Table 3.

[0089] Table 3 Performance test results

[0090]

[0091]

[0092] Note: In the table, a means that there is a significant difference between the experimental toothpaste groups 1-4 and the control group (p < 0.05); b means that there is a significant difference between the experimental toothpaste groups 5-14 and the experimental toothpaste group 4 (p < 0.05).

[0093] Result analysis:

[0094] According to the results, the copper consumption values ​​of toothpastes 1-4 are lower than those of the control group, and the degree of tooth wear is also relatively low, which effectively protects the tooth enamel. At the same time, the cleanliness is significantly higher than that of the control group (p < 0.05), which is statistically significant, indicating that the beads of sustained-release active substances provided by the present invention have certain friction and excellent cleaning power. The reasonable combination of edible gum components makes the entire system of sustained-release beads have certain coating and stability, forming a polysaccharide carrier with coating and stability. The mica in the filling component can effectively buffer the friction of titanium dioxide, slow down the wear of titanium dioxide on tooth enamel, and at the same time play a cleaning role. By comparing toothpastes 1-4 and toothpastes 5-14 in the experimental group, it can be seen that reducing any component in the edible gum component and / or reducing any component in the filling component will affect the overall performance of the toothpaste.

[0095] Plaque removal test

[0096] Samples and experimental groups:

[0097] Control group: toothpaste was prepared according to the formula of the control group in Table 2;

[0098] Experimental group 1: toothpaste was prepared according to experimental toothpaste group 4 in Table 2;

[0099] Experimental group 2: Bletilla striata root extract, amelogenin and Alpinia oxyphylla extract were directly added to the control group formula in Table 2 at an addition amount of 0.03wt%, 0.00005wt% and 0.05wt% respectively to prepare toothpaste, without sustained-release beads coating Bletilla striata root extract, amelogenin and Alpinia oxyphylla extract;

[0100] Experimental group 3: preparing sustained-release beads 15, wherein the active component lacks the extract of Bletilla striata root, and the rest is consistent with the formula of sustained-release beads 4 in Table 1, and adding the sustained-release beads 15 at an addition amount of 50wt% to the formula of the control group in Table 2 to prepare toothpaste;

[0101] Experimental group 4: preparing sustained-release beads 16, wherein the active component lacks the Alpinia oxyphylla extract, and the rest is consistent with the formula of sustained-release beads 4 in Table 1, and adding the sustained-release beads 16 at an addition amount of 50wt% to the control group formula in Table 2 to prepare toothpaste;

[0102] Experimental plan: There were 80 subjects in the experiment, with 20 subjects in each group, aged between 45 and 60 years old, with relatively consistent periodontal conditions, appropriate levels of dental plaque, more than 20 detectable teeth, and no other similar studies were participated in at the same time. The indicators of the baseline examination of the experimental group and the control group were in the same distribution range (P>0.05). Before using toothpaste (D0), the subjects used plaque indicators to perform a baseline plaque index examination and record. On the 7th day (D7), the plaque index was re-examined and recorded.

[0103] SPSS statistical software was used for data processing, independent sample t test was used for comparison between groups in the same period, and paired sample t test was used for longitudinal comparison within the group. Based on the statistical experimental data, it was calculated whether there was statistical significance in the removal of dental plaque between the experimental group and the control group, and before and after the use of the sample in the experimental group. The experimental results are shown in Table 4.

[0104] Table 4 Statistical analysis results of plaque index

[0105]

[0106] Note: "a" in the table indicates that the plaque index before and after using toothpaste is significantly different (p < 0.05); "b" in the table indicates that the plaque index after using toothpaste of experimental group 1 for 7 days is significantly different from that after using toothpaste of control group for 7 days (p < 0.05).

[0107] Result analysis:

[0108] According to the experimental results, the toothpastes of the control group and the experimental group have a certain effect on removing dental plaque and have a certain effect on controlling plaque; the toothpaste of the experimental group 1 prepared according to the technical scheme provided by the present invention and containing sustained-release active composition beads has better effects on removing dental plaque and controlling plaque than other groups, among which the beads of the experimental groups 3 and 4 have weakened effects on removing dental plaque when lacking the extract of the root of Bletilla striata or the extract of the seed of Alpinia oxyphylla; the results of the experimental group 2 show that the method of directly adding active components to the toothpaste is less effective than the method of coating the active components with sustained-release beads and then adding them to the toothpaste. This is because the active ingredients can act directly on the tooth surface during the friction process along with the sustained-release beads. Compared with the method of directly adding the active substance, the active substance has no linkage with the abrasive and cannot effectively adhere to the tooth surface to form an active layer.

[0109] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A bead for sustained release of an active composition, characterized in that: The invention comprises components: an active composition, a colloid component, a filling component, a moisturizer, a preservative and a solvent; The active composition is composed of Bletilla striata root extract, amelogenin and Alpinia oxyphylla seed extract; The colloid component consists of sodium alginate and edible gum; The edible gum is a composition of xanthan gum, gellan gum and agar; the mass ratio of the xanthan gum, gellan gum and agar is (0.1-1): (1-2): (1-2); The filling component is composed of mica, titanium dioxide and iron oxides; the mass ratio of mica, titanium dioxide and iron oxides is (65-87): (5-16): (8-19); The moisturizing agent is at least one of glycerin, propylene glycol, sodium hyaluronate, and Tremella polysaccharide; The preservative is at least one of phenoxyethanol, methylparaben, p-hydroxyacetophenone, and caprylhydroxamic acid; The solvent is deionized water; The sodium alginate is added in an amount of 0.25-2.0wt% in the beads; The edible glue is added in an amount of 0.5-2.0wt% in the beads; The filling component is added in an amount of 0.1-2.0 wt % in the beads.

2. The beads for sustained-release active composition according to claim 1, characterized in that: The particle size of the beads is 1000-4000 μm.

3. The method for preparing beads of the sustained-release active composition according to claim 1 or 2, characterized in that: The following steps are involved: S1. Mix deionized water, sodium alginate and edible gum and heat to 80-100°C to dissolve to obtain a mixed solution A; S2. The active composition was uniformly dissolved in deionized water to obtain a mixed solution B; S3. The filling component, preservative, and moisturizer are added to the mixed solution A and mixed evenly to obtain a mixture C; S4. The mixed solution B obtained in step S2 is added to the mixed solution C, and the mixture is stirred and dispersed uniformly to obtain a mixed solution D; S5. The mixed solution D is dripped into the incompatible condensation reaction liquid through a dripping device to quickly form gel beads, and the formed beads are washed with water and then sealed and immersed in a preservative solution to obtain beads of the sustained-release active composition, wherein the preservative solution is prepared from phenoxyethanol, methylparaben and 95v / v% ethanol aqueous solution.

4. A toothpaste, characterized in that: Beads comprising the sustained-release active composition of claim 1 or 2; The beads are added in an amount of ≤50 wt % in the toothpaste.

5. The toothpaste according to claim 4, characterized in that It also contains abrasives, humectants, foaming agents, thickeners, fragrances, preservatives, anti-tartar agents, pH adjusters, sweeteners, anti-caries agents, and solvents.

6. Use of the beads of the sustained-release active composition according to claim 1 or 2 in the preparation of an oral cleaning preparation having anti-caries, anti-inflammatory and antibacterial effects.

Citation Information

Patent Citations

  • Toothpaste with low abrasion and high tooth cleaning effect

    CN107982185A

  • Oral cleaning composition and application thereof

    CN117815111A